Evaluation of the antibacterial effects of vancomycin hydrochloride released from agar-gelatin-bioactive glass composites - Rivadeneira, Josefina; Laura Di Virgilio, Ana; Carina Audisio, M.; Boccaccini, Aldo R.; Gorustovich, Alejandro A. (Biomedical Materials (Bristol), 2015)
The aim of this work was to evaluate the perfomance of agar-gelatin (AG) composites and AG-containing 45S5 bioactive glass (BG) microparticles (AGBG) in relation to their water uptake capacity, sustained release of a drug over time, and antibacterial effects. The composites were fabricated by the gel-casting method. To impart the local drug release capacity, vancomycin hydrochloride (VC) was loaded in the composites in concentrations of 0.5 and 1 mg ml. VC release was assessed in distilled water at 37 °C up to 72 h and quantified spectrophotometrically. The antibacterial activity of composites was evaluated by the inhibition zone test and the plate count method. The experiments were performed in vitro up to 48 h on three staphylococcus strains: Staphylococcus aureus ATCC29213, S. aureus ATCC6538 and Staphylococcus epidermidis ATCC12228. The results showed that the addition of BG to AG composites did not affect the degree of water uptake. The release of VC was significantly affected by the presence of BG. VC release was higher from AGBGVC films than from AGVC ones over prolonged incubation times. Bacterial inhibition zones were found around the composites. The halos were larger when the cells were put in contact with AGVC composites than when they were put in contact with AGBGVC ones. Nevertheless, the viable count method demonstrated that the composites inhibited Staphylococcus cell growth with no statistical differences. In conclusion, the addition of BG did not reflect an improvement in the parameters studied. On the other hand, composites loaded with VC would have a role in prophylaxis against bacterial infection.
Keywords: bioactive glass; biopolymers; staphylococci; vancomycin hydrochloride